Nurses’ Job Satisfaction in Chosen Private Hospitals in Isabela Province - Rianne Maie C. Mangaoil; Angelito E. Alvarado; Mariell Anne F. Angoluan; Hazel Joy G. Apaga; Danica D. Ariola; Jonalyn B. Balauro; Haziel Claire C. Ballad; Viell Marie S. Pecson (Health Notions, 2021)
Job satisfaction has been the motivational factor every employee aspires in order to enjoy and develop passion in performing their job efficiently and effectively.  This study aims to determine the job satisfaction of registered nurses in chosen Private Hospitals in Isabela, Province. This Quantitative research, a descriptive correlational study conducted among 30 nurses who works in the said place through accidental sampling technique. The questionnaire used is a researcher-made consists of two parts, the profile of the respondents and the nurse's job satisfaction parameters through a likert scale. Findings shows through Pearson’s chi-square C test at 0.05 level of significance that Nurses in chosen Private Hospitals in  Isabela showed no significant relationship between job satisfaction profile. It is concluded when grouped according to their profile, where C>.05 analysis,  that there is no significant relationship between the respondents’ job Satisfaction and their profile, these parameters do not influence their job satisfaction. However, for the position of the respondents; the significance C value was less than 0.05; this means that there is a significant relationship between the job satisfaction of the respondents and their position. This study will help the Private Hospitals to determine the factors that influence the job satisfaction of the nurses.Keywords: job satisfaction; registered nurse; private hospitals in Isabela